Supporting local planning and innovation in the Nile BDC—group feedback - Tucker, Josephine (International Livestock Research Institute, 2011)
In early May 2011, people working on the Nile Basin Development Challenge (http://nilebdc.org) met in Addis Ababa in a 'science and reflection workshop'. Session 2 of the workshop examined institutional and other processes that are key to success of the overall program. In this video, Josie Tucker (ODI) reports from small group discussions on ways to support more flexible and participatory implementation of rainwater management and innovation at the local and regional levels.